Spatio-temporal geochemical evolution of the SE Australian upper mantle deciphered from the Sr, Nd and Pb isotope compositions of Cenozoic intraplate volcanic rocks - Oostingh, K.; Jourdan, Fred; Merle, R.; Chiaradia, M. (Oxford University Press, 2016)
Intraplate basaltic volcanic rocks ranging in age from Late Cretaceous to Holocene are distributed across southeastern Australia in Victoria and eastern South Australia. They comprise four provinces differentiated on the basis of age and spatial distribution. The youngest of these (<4·6 Ma) is the Newer Volcanic Province (NVP), which incorporates lava flows, scoria cones and maars, distributed across western and central Victoria into South Australia. The oldest eruptive rocks belong to the 95-19 Ma Older Volcanic Province, which comprises basaltic lava flows and shallow intrusions distributed across eastern and central Victoria. When examined within the broader framework of geochemical data available for Cretaceous to Cenozoic intraplate volcanism in southeastern Australia, new major, minor and trace element and Sr, Nd and Pb isotope analyses of volcanic rocks from the NVP suggest that their parental magmas originated from a distinctively different mantle source compared with that of the Older Volcanics. We propose that the magmas represented by the Older Volcanics originated from low degrees of partial melting of a mixed source of Indian mid-ocean ridge basalt (MORB)-source mantle and calcio-carbonatite metasomatized sub-continental lithospheric mantle (SCLM), followed by up to 20% fractional crystallization. The magmas of the youngest (<500 ka) suite of the NVP (the Newer Cones) were generated by up to 13% partial melting of a garnet-rich source, followed by similar degrees of fractional crystallization. We also suggest that the temporally intermediate Euroa Volcanics (~7 Ma) reflect chemical evolution from the source of the Older Volcanics to that of the Newer Cones. Furthermore, energy-constrained recharge, assimilation and fractional crystallization (EC-RAxFC) modelling suggests that the Sr isotope signature of the ~4·6-1 Ma Newer Plains component of the NVP can be explained by up to 5% upper crustal assimilation. On the basis of these results and data from the literature for mantle xenoliths, we propose a geodynamic model involving decompression melting of metasomatized veins at the base of the SCLM generating the Older Volcanics and modifying the ambient asthenosphere of Indian MORB isotope character. This was followed by thermal erosion and entrainment of the resulting depleted SCLM into the modified Indian MORB-source asthenospheric mantle, generating the Newer Cones. Such a model is in agreement with recent geophysical observations in the area suggesting edge-driven convection with shear-driven upwelling as a potential geodynamic model resulting in temporal upwelling in the region.